Community based mangrove planting handbook for Papua New Guinea. (Metro Manila, Philippines Asian Development Bank, 2018)
This publication is an initiative of the Government of Papua New Guinea that presents a step-by-step guide on how to rehabilitate mangroves.The initiative aims to address the impacts of climate change, particularly coastal flooding which is prevalent in Papua New Guinea. The idea was to design a handbook on planting mangroves for all purposes, including carbon absorption, nature conservation, fisheries, and ecotourism.
Keywords: Mangrove forests -- Papua New Guinea; Mangrove management -- Papua New Guinea; Climate change mitigation -- Papua New Guinea; Electronic books